Changes in Electrical Activity of the Masseter Muscle and Masticatory Force after the Use of the Masseter Nerve as Donor in Facial Reanimation Surgery - Jose E. Telich-Tarriba; Alejandro Orihuela-Rodríguez; Adriana de Lourdes Rivera-Priego; Fernando Ángeles-Medina; Julio Morales-González; Ignacio Mora-Magaña; Adriana Fentanes-Vera; Damian Palafox; Alexander Cárdenas-Mejía (Indian Journal of Plastic Surgery, 2020)
Introduction The masseter nerve has been used as a donor nerve for facial reanimation procedures due to the multiple advantages it offers; it has been generally considered that sacrifice of the masseter nerve does not alter the masticatory apparatus; however, there are no objective studies to support this claim. Objective To evaluate the impact that the use of the masseter nerve in dynamic facial reconstruction has on the electrical activity of the masseter muscle and on bite force. Materials and Methods An observational and prospective longitudinal study was performed measuring bite force and electrical activity of the masseter muscles before and 3 months after dynamic facial reconstructive surgery using the masseter nerve. An occlusal analyzer and surface electromyography were employed for measurements. Results The study included 15 patients with unilateral facial paralysis, with a mean age of 24.06 ± 23.43. Seven patients were subjected to a masseter–buccal branch nerve transfer, whereas in eight patients, the masseter nerve was used as a donor nerve for gracilis free functional muscle transfer. Electrical activity of the masseter muscle was significantly reduced after surgery in both occlusal positions: from 140.86 ± 65.94 to 109.68 ± 68.04 (p = 0.01) in maximum intercuspation and from 123.68 ± 75.64 to 82.64 ± 66.56 (p = 0.01) in the rest position. However, bite force did not show any reduction, changing from 22.07 ± 15.66 to 15.56 ± 7.91 (p = 0.1) after the procedure. Conclusion Masseter nerve transfer causes a reduction in electromyographic signals of the masseter muscle; however, bite force is preserved and comparable to preoperative status.